2015
DOI: 10.1002/hed.23975
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CD133 in the enhancement of chemosensitivity in oral squamous cell carcinoma–derived side population cancer stem cells

Abstract: Side population cells with CSCs properties existed in OSCCs, and silencing CD133 exhibited a prominent therapeutic effect in enhancing the sensitivity of chemotherapy in OSCC through elimination of CSCs. © 2015 Wiley Periodicals, Inc. Head Neck 38: E231-E238, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
(95 reference statements)
0
56
0
Order By: Relevance
“…However, to date, few CSC markers in OSCC have been identified (29,30). The results of the current study indicate that SOX2, KLF4 and brachyury may present clinically useful CSC markers, and their expression levels may be prognostic factors for OSCC.…”
Section: Discussionmentioning
confidence: 58%
“…However, to date, few CSC markers in OSCC have been identified (29,30). The results of the current study indicate that SOX2, KLF4 and brachyury may present clinically useful CSC markers, and their expression levels may be prognostic factors for OSCC.…”
Section: Discussionmentioning
confidence: 58%
“…Nevertheless, various lines of evidence suggest that CD133 is not only a surface marker but it also plays a causal role in CSC. For example, CD133 is required for the maintenance of glioblastoma stem cells [131] and confers stem-like properties and chemoresistance to other cancer cell types [133135]. Experimental data implicated the PI3K/Akt pathway as a CD133 effector [133, 134, 136].…”
Section: Main Textmentioning
confidence: 99%
“…Recent studies have revealed that cancer stem cells (CSCs) or termed tumor initiating cells (TICs) with tumors could contribute to tumor maintenance, metastasis, radio-resistance and chemo-resistance in a variety of cancers, including OSCC [611]. Moreover, the first connection of between CSCs and epithelial-mesenchymal transdifferentiation (EMT), a dynamic process in which cells lose epithelial features and gain mesenchymal properties, is demonstrated in breast cancer stem cells model [12].…”
Section: Introductionmentioning
confidence: 99%